The Development of Contemporary Local Cuisine Recipe of Ban Tai Community to Promote Tourism of Koh Samui, Surat Thani Province - Naksawat, Napat; Khunrit, Mantanan (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
The objectives of this research were 1) to examine participatory identities of food security in the Ban Tai community, 2) to develop a contemporary local cuisine recipe made with ingredients from the Ban Tai community, and 3) to study the satisfaction of contemporary recipes from raw materials in the Ban Tai community using a mixed research method. Collect data from surveys, interviews, and focus groups. Key Informants who have knowledge and roles in tourism development and the Ban Tai community selected the target groups to collect specific data, totaling 20 people using content analysis. The quantitative data were questionnaires to collect data with a random sampling method surveying 400 tourists and locals in Koh Samui. For data analysis, descriptive statistics including parsing percentage, mean and standard deviation were used. The results of the study were as follows: 1) There are three participatory identities of food security in the Ban Tai community: (1) food availability; (2) food access; and (3) food utilization; 2) The contemporary local cuisine recipe made with ingredients from the Ban Tai community can be divided into six groups, including (1) snacks, (2) main dishes, (3) desserts, (4) beverages, (5) various dishes, and (6) the 20 best dishes to eat in the Ban Tai community; and 3) the satisfaction level of contemporary recipes made from raw materials in the Ban Tai community. It was found that the most satisfied aspect had an average of 4.95 and a standard deviation of 0.21 can be used to promote tourism and increase the economic and social value of the community in the future.